Nursing contributions to the access to health care for deaf people (Research, Society and Development, 2022)
The Brazilian Sign Language - Libras, was nationally recognized as the second official language of the country, even so, the person with hearing impairment experiences the frequent loss of identity resulting from the difficulty of communication with the society mostly composed of listeners. Such obstacles expose the deaf person to situations of vulnerability and social risk, to highlight the access to health services, essential for the maintenance of physical integrity, psychological and social human beings.  Therefore, this paper aims to understand how the nursing team can contribute to the access to health services for deaf people. This is a literature review of integrative type and qualitative approach, through the bibliographic search in scientific databases LILACS, MEDLINE, BDENF and SciELO, and analysis of scientific research published in full, from 2011 to 2021, in the Brazilian Portuguese language, in order to limit the information to the Brazilian reality. The research used to prepare this project shows the difficulty of patient communication at the time of nursing consultations, negatively impacting the reception and continuity of care of this patient. It is concluded that nurses have much to contribute to the guarantee of the social right to health, commonly denied to the deaf person. However, in order to offer an integral and efficient service, the nursing professional must be trained to do so.